1988
DOI: 10.1002/aic.690341209
|View full text |Cite
|
Sign up to set email alerts
|

Theories of precipitation induced by dissolution

Abstract: When a porous solid is placed in acid, the solid dissolves at its surface. However, the same solid can precipitate or dissolve in pores inside the solid. The internal precipitation is a consequence of a nonlinear solubility product amplified by fast chemical kinetics. The internal dissolution can be enhanced by unequal diffusiQn coefficients. Both precipitation and dissolution can occur simultaneously but in different regions, mimicking the patterns of mineral found in teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For example, Cussler and Featherstone (1981), Cussler (1982), and Cussler et al (1983) showed that dissolution at the surface of such solids can lead to both precipitation and dissolution in different regions within the solid. Later, Kopinsky et al (1988) extended the above work and examined a system with one dissolution front from a finite-rate perspective and also relaxed some of the assumptions made in the previous studies. More elaborative models have been derived by Lichtner et al (1986a,b) and Novak et al (1989).…”
Section: Development Of the Modelmentioning
confidence: 95%
“…For example, Cussler and Featherstone (1981), Cussler (1982), and Cussler et al (1983) showed that dissolution at the surface of such solids can lead to both precipitation and dissolution in different regions within the solid. Later, Kopinsky et al (1988) extended the above work and examined a system with one dissolution front from a finite-rate perspective and also relaxed some of the assumptions made in the previous studies. More elaborative models have been derived by Lichtner et al (1986a,b) and Novak et al (1989).…”
Section: Development Of the Modelmentioning
confidence: 95%
“…the A + profile in Figures 2a, 6a, 8-10). Kopinsky et al (1988) equilibrium so that argument is inapplicable here. Our interpretation, given primarily with reference to Figure 2a, is as follows.…”
Section: Local Maxima In Aqueous Profilesmentioning
confidence: 98%
“…introduction Diffusion-induced mineral zonation is an important phenomenon in metasomatic processes (processes involving changes in the chemical composition of rock), causing replacement of an initial suite of minerals in a permeable medium with one or more regions of different mineral combinations. Systems such as the dissolution of hydroxyapatite (Kim and Cussler, 1987) have been experimentally examined, and some geochemical systems have been analyzed mathematically (Cussler et al, 1983;Lichtner et al, 1986 a, b;Kopinsky et al, 1988). While the convection-dominated analog to this problem has been studied extensively (Bryant, 1986;Bryant et al, 1986Bryant et al, , 1987Dria, 1988;Lichtner, 1985;Schechter et al, 1987;Walsh, 1983;Walsh et al, 1982Walsh et al, , 1984, the diffusion-only regime has not received the same rigorous treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such arguments can also hold here. Kapinsky et al have shown that, if the reactions are fast and reversible, then reprecipitation can occur during dissolution. The process of surfactant aggregation is generally taken to be a fast reversible reaction.…”
mentioning
confidence: 99%